If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a * 2 + yx = 7 Reorder the terms for easier multiplication: 3 * 2a + yx = 7 Multiply 3 * 2 6a + yx = 7 Solving 6a + xy = 7 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1xy' to each side of the equation. 6a + xy + -1xy = 7 + -1xy Combine like terms: xy + -1xy = 0 6a + 0 = 7 + -1xy 6a = 7 + -1xy Divide each side by '6'. a = 1.166666667 + -0.1666666667xy Simplifying a = 1.166666667 + -0.1666666667xy
| 6(x-4)=8x-28 | | 4*(x+1)=2*(5-3x) | | 6+3a= | | 7u-36=3(u-8) | | t^2-60t=-450 | | t^2+60t=-450 | | -3*-3+6+2= | | 14(6x+16)= | | 3*3+6+2= | | 5+7(2b-2b)=5 | | y(25+-.75y)=350 | | x^2+y^2+6x-14y+42=0 | | 42-21x=63-7y | | (6xy+7)dx+(3x^2-2)dy=0 | | 6x+9-x+19= | | 4x+10=-42-8x | | 3n=34 | | 17x-2x=7x+11 | | 7x+13=3x+65 | | 4x+38=180 | | 2(x-3)(x-3)+3=13 | | 2(x-3)+3=13 | | x^4-x^3-2x^2+4x-24=0 | | (X^2+24)= | | 3x^2-11x-3=-x^2 | | Un=5+(0.1n-0.1) | | Un=5+(0.1n+0.1) | | Cos(5x)-cos(9x)=0 | | z^2-(3-2i)z+(5-5i)=0 | | 6x=n+4 | | 4x^2+12x+9=49x | | 4x^3+12x+9=49x |